Implementation of Blocking Function in Web Based Charity Management System - LEE, ZHI HAN; Abd Ishak, Suhaimi (Applied Information Technology And Computer Science, 2023)
Due to the Covid-19 pandemic many people are facing difficulties such as financial problem and it is not efficiency for event organizer to manage the event using social media and difficult for volunteers to search for charity events using the same method. The charity management system can simplified the participation process for the volunteers at the same time provide convenience for the event organizer to manage the event. The charity management system will be developed using HTML, CSS, and C# with ASP.NET framework and is compiled using Microsoft Visual Studio and Microsoft Server SQL. Volunteers can participate in a charity event and make donation to a fundraising through this system while event organizer can create and manage their event. Beside that, blocking function was implemented where blocked users cannot participate or create new event to reduce the case of scammer and uncooperative volunteers.